Deskripsi Kunjungan Kapal Penangkap Ikan di Pelabuhan PPI Tanjung Limau Kota Bontang - Mohammad Alif Syahrizan; Elly Purnamasari; Juliani (2339-1324, 2024)
The purpose of this study is to find out the types of ship specifications, types of fishing gear, fishermen's catches and facilities at the PPI Tanjung Limau Port, Bontang City. Primary data were taken in March 2022, sampling using the purposive sampling method with a total sample of 30 respondents. The research data were analyzed by analytical descriptive qualitative methods. The results showed that the specifications of fishing ships have Grosee Tone (GT) ranging from 1 - 30 GT with the types of engines used are Mitsubishi, Domfeng and Jhiandong. The types of fishing gear used by fishermen are serok, tonda fishing rod, purse seine, transporter, swamp fishing rod, and gill net. The types of fish caught are skipjack tuna, kite fish, bawis fish and snapper. The fisheries facilities at PPI Tanjung Limau consist of 3 classification sections, namely basic facilities, functional facilities and supporting facilities. Keywords : PPI Tanjung Limau, Ships, Fishing Gear, Catches and Fisheries Facilities